KOMPARATIF HASIL BELAJAR MAHASISWA REGULER DENGAN MANDIRI PENDIDIKAN TEKNIK INFORMATIKA FT-UNP - Rido Putra; Edidas Edidas (Universitas Negeri Padang, 2019)
Padang State University is a state university that was established in West Sumatra with various faculties including engineering faculties in charge of various departments, one of which is electronics engineering majors consisting of electronics engineering study programs, electronic engineering education programs and informatics and computer engineering education courses . Various assumptions emerged with student admissions from both the regular and independent lane. To answer these assumptions, a study was conducted aimed at looking at a comparison of learning outcomes between regular entry students and regular independent entry pathways through a cumulative grade point average (GPA) which was carried out through hypothesis testing and research prerequisites for data sources obtained from descriptive data on students of educational study programs informatics and computer engineering so that it is known between semester credit (X) with the Grade Point Average (GPA) of significance value 0.409 for regular students and a significance value of 0.258 for independent regular students. It was concluded that there was a Positive and Significant Relationship between Regular students and Independent Selection students Informatics and Computer Engineering Education in 2014-2017 and there were no significant differences in learning outcomes in the January-June 2017 semester, in the form of GPA.Keywords: Student, learning outcomes, comparison, population and sample, hypothesis testing.